Analisis Perbandingan Sistem Bengkel Berbasis Dekstop dan Web Menggunakan Metode User Acceptance Testing - Muhammad Surya Affandi; Rudi Setiyanto; Makmun ZA (JSAI (Journal Scientific and Applied Informatics), 2025)
This study aims to compare desktop-based and web-based workshop information systems at PT. Motoreko Mobilindo using the User Acceptance Testing (UAT) method. The evaluation was conducted based on five key indicators: ease of use, access speed, reliability, security, and user satisfaction. Data were collected through questionnaires filled out by active users who had experience with both systems. The results show that the desktop system excels in terms of access speed (96%), reliability (97%), and security (99%). Meanwhile, the web system outperforms in ease of use (97%) and user satisfaction (96%). These findings indicate that although the desktop system has more stable technical performance, the web system is more widely accepted by users due to its convenience and flexibility. This study recommends a hybrid approach as a strategic solution, by maintaining the technical strengths of the desktop system while integrating the accessibility benefits of the web system. Thus, the company can develop a balanced, adaptive information system that aligns with the needs of digital transformation.